The role of hybrid learning spaces in enhancing higher education students’ employability - Bennett, Dawn; Knight, E.; Rowley, J. (WILEY, 2020)
Graduate employment rates and self-reported employability are increasingly a feature of higher education funding measures. However, graduate outcomes do not denote the whole learning experience of the student nor is the student experience reducible to a single statistic. This paper discusses a design-centric approach to employability development which was enacted within a hybrid learning space. The study engaged 52 final-year speech pathology students, their lecturer, the lead researcher and a career practitioner (advisor) at an Australian university. Students first created personalized employability profiles using an established online self-reflection tool. The online tool produced a personalized report and enabled students to access developmental resources relating to employability and student success. The project team used anonymized student data to transform a previously generic “careers” workshop into a targeted workshop in which students explored individual and cohort findings and participated in developmental activities informed by the data. The initiative’s contribution to learning space research is in its composition as a hybrid learning space in which educators and students engaged as learners and developers of their online learning spaces, and educators collaborated to analyze student data and inform learning and teaching enhancements within the same study period. It is anticipated that the data from subsequent years will inform the curricular review, particularly if subsequent student cohorts express similar concerns. Implications for higher education policy and practice are discussed.